2019
DOI: 10.1186/s12938-019-0725-3
|View full text |Cite
|
Sign up to set email alerts
|

Automatic sleep stage classification based on subcutaneous EEG in patients with epilepsy

Abstract: Background The interplay between sleep structure and seizure probability has previously been studied using electroencephalography (EEG). Combining sleep assessment and detection of epileptic activity in ultralong-term EEG could potentially optimize seizure treatment and sleep quality of patients with epilepsy. However, the current gold standard polysomnography (PSG) limits sleep recording to a few nights. A novel subcutaneous device was developed to record ultralong-term EEG, and has been shown to measure even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Additionally, we are looking to test the algorithm with data obtained from humans and other animal models, but there is recent work using similar approaches that lead us to believe our method can be effective in other models. 55,56 Indeed, a recent study demonstrated that another supervised learning algorithm, deep convolutional neural networks, can be used to predict sleep stages from manually scored data in narcoleptic mice with a comparable degree of success as our own approach. 57 An additional value of this work is the characterization of the features we use to train our model and score recordings.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, we are looking to test the algorithm with data obtained from humans and other animal models, but there is recent work using similar approaches that lead us to believe our method can be effective in other models. 55,56 Indeed, a recent study demonstrated that another supervised learning algorithm, deep convolutional neural networks, can be used to predict sleep stages from manually scored data in narcoleptic mice with a comparable degree of success as our own approach. 57 An additional value of this work is the characterization of the features we use to train our model and score recordings.…”
Section: Discussionmentioning
confidence: 92%
“…This highlights the ability of such systems to differentiate awake from sleep states. 22 Even with long-term averaging, peaks in oscillatory activity were seen. The most prevalent diurnal peak appeared in the alpha range (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One study has even shown that two-channel subscalp EEG is sufficient to do robust sleep staging. 71,72 | 1813 DUUN-HENRIKSEN Et al.…”
Section: Using Subscalp Eeg In the Futurementioning
confidence: 99%
“…Furthermore, as a relationship between sleep quality/duration and seizure risk has been suggested, the ability to record objective sleep quality and seizures is critical to understanding whether strategies to improve sleep can help seizure control. One study has even shown that two‐channel subscalp EEG is sufficient to do robust sleep staging 71,72 …”
Section: Utility Of Subscalp Eeg Recordingmentioning
confidence: 99%